Diffuse Melanosis and Ascites due to Metastatic Malignant Melanoma. (2008) - Sendagorta, Elena; Pizarro, Angel; Feito, Marta; Mayor, Matias; Ramírez, Paloma; Floristán, Uxua; Feltes, Rosa
Abstract : We present a female patient who developed mucosal and skin hyperpigmentation due to metastatic malignant melanoma. Diffuse cutaneus melanosis is a rare entity that complicates a small percentage of metastatic melanomas, confering a fatal prognosis. We discuss briefly the current evidence on pathogenesis of melanosis arising from metastatic melanoma.